Determinan Perilaku Pemeriksaan HIV pada Wanita Penjaja Seks Langsung di Eks Lokalisasi - Sari, Nirma Lidia (Poltekkes Kemenkes Tanjung Karang, 2022)
HIV testing is the most important entry point in HIV/AIDS prevention, care, support, and treatment services. In implementing HIV/AIDS and STI control, the government recommends re-testing for HIV at least once every 6 months in groups with high-risk behavior. However, the coverage of HIV testing in key populations vulnerable to HIV infection, including Direct Female Sex Workers (DFSW) is still low. The purpose of this study was to determine the factors associated with HIV testing behavior among DFSW. The sample in this study amounted to 103 people. Data were analyzed using univariate, bivariate, and multivariate multiple logistic regression methods. The test results showed that the source of the information was related to HIV testing (p-value 0.045); odds ratio 4.401. Peer support was related to HIV testing (p-value 0.023) odds ratio 5.22. Support from field officers was related to compliance with HIV testing (p-value 0.000); odds ratio 19.02. There are two confounding variables, namely health worker support (p-value 0.28); odds ratio 3.747 and attitude (p-valule 0.242); odds ratio 0.461 as a protective factor. From the results of the analysis, it was found that field staff variables had more influence on HIV testing. Efforts to improve HIV testing behavior are carried out by increasing the number of information sources that are presented as attractive as possible. The role of field officers and peers as partners in encouraging DFSW to carry out HIV testing needs to be increased.